1983
DOI: 10.1007/bf00982219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allelopathic substances produced by asparagus on incidence and severity of asparagus decline due toFusarium crown rot

Abstract: The effects of toxic components isolated from asparagus tissue onFusarium spp. and other soil microorganisms and their effects on the susceptibility of asparagus toFusarium crown rot was investigated to determine what role allelopathic substances may play in the asparagus ecosystem and in asparagus crown rot decline. Dried sterilized asparagus crown and root tissues were incorporated into pots of 3-month-old asparagus seedlings with and withoutFusarium inoculum. Root tissue alone and treatments in which crown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 5 publications
1
41
0
1
Order By: Relevance
“…Early work by Young in Taiwan (1981,1983-1985,1984,1985 focused on the exudates of asparagus roots and extracts from asparagus soils which were collected using XAD^t resin. These extracts inhibited the growth of asparagus seedlings and inhibition was correlated with phenolic content of the extract.…”
Section: H92063mentioning
confidence: 99%
See 1 more Smart Citation
“…Early work by Young in Taiwan (1981,1983-1985,1984,1985 focused on the exudates of asparagus roots and extracts from asparagus soils which were collected using XAD^t resin. These extracts inhibited the growth of asparagus seedlings and inhibition was correlated with phenolic content of the extract.…”
Section: H92063mentioning
confidence: 99%
“…It was found that inhibition decreased with time and that the activity was located in material which fluoresced under UV light and also reacted with phenolic sensitive reagents. Hartung et al (1983Hartung et al ( , 1986Hartung et al ( , 1989. examined the effects of extracts from asparagus tissue on the growth of seedlings of various species and also the combined effect of autotoxins and Fusarium spp.…”
Section: H92063mentioning
confidence: 99%
“…An interaction of root autotoxin with the two common Fusarium species affecting asparagus was first reported by Hartung & Stephens (1983). They found that neither Fusarium nor root fragments alone reduced dry weight of asparagus seedlings appreciably, but when combined they significantly decreased dry weight and increased root rot of seedlings.…”
Section: Autotoxinsmentioning
confidence: 97%
“…More recent reports describe how crude extracts from asparagus roots have a negligible effect on seedling germination but dramatically reduce radicle elongation ofasparagus and several other plant species (Hartung & Stephens 1983;Shafer & Garrison 1986;Hazebroek et al 1989). …”
Section: Autotoxinsmentioning
confidence: 99%
“…Similarly, under laboratory conditions almost any degree of water stress seems to lower the ferulic acid-inhibition threshold on germination or seedling growth (96). In some cases the pathogenesis of disease organisms, such as root rot fungi, is increased by allelopathic effects from decomposing plant residue (104)(105)(106).…”
Section: Quantity Of Allelochemicals Some Of the Pioneer Investigatimentioning
confidence: 99%